Efek Asupan Antioksidan Kaya Enzim Cytochrome P450 2E1 (CYP2E1) Terhadap Kadar Leukosit - Baharuddin M. Subandi; Suardi Zurimi; Abdul Rohim Tualeka; Nanda Bella Puspitaloka (Direktorat Politeknik Kesehatan Makassar, 2024)
The human body has an enzymatic antioxidant system, but its capacity is not always sufficient when the amount of free radicals is excessive. The approach of consuming antioxidants rich in the CYP2E1 enzyme is used to help the body detoxify benzene metabolites so they can be excreted from the body. The aim of this study is to analyze the effect of consuming antioxidants rich in the CYP2E1 enzyme on changes in leukocyte levels among workers in the Tambak Osowilangun Surabaya home-based shoe industry. This type of research is a pre-experimental study using a one-group pre-test post-test design. The sample used in this study was total population sampling, consisting of all 27 workers in the Tambak Osowilangun home-based shoe industry. The intervention provided was in the form of antioxidant supplements in powder form, with a dosage of 15 grams, consumed twice a day for 5 consecutive days. Leukocyte levels were measured by taking blood samples from the workers on the first day before the intervention and on the fifth day after the intervention. The results of the study showed changes in the leukocyte levels of all workers after the treatment. There was an increase in the number of workers who reached normal leukocyte levels (92.6%). However, some workers did not reach normal leukocyte levels (7.4%) despite experiencing changes in their leukocyte levels. The conclusion of this study is that the intervention was effective in normalizing the workers' leukocyte levels, particularly in female workers, those of productive age, with normal BMI, non-smokers, those who engage in physical activity/exercise, and those who do not use personal protective equipment (PPE). It is recommended that workers regularly engage in exercise that suits their preferences and body needs, adopt a balanced diet, consume foods rich in antioxidants, use brushes when applying glue, and use standard PPE such as N95 masks, gloves, and aprons.. Keywords: leukocyte count; antioxidant; CYP2E1